The characteristics of behaviour change interventions used among Pacific people: a systematic search and narrative synthesis - Amio Matenga-Ikihele; Judith McCool; Rosie Dobson; Fuafiva Fa'alau; Robyn Whittaker (BMC, 2021)
Abstract Background Pacific people living in New Zealand, Australia, United States, and the Pacific region continue to experience a disproportionately high burden of long-term conditions, making culturally contextualised behaviour change interventions a priority. The primary aim of this study was to describe the characteristics of behaviour change interventions designed to improve health and effect health behaviour change among Pacific people. Methods Electronic searches were carried out on OVID Medline, PsycINFO, PubMed, Embase and SCOPUS databases (initial search January 2019 and updated in January 2020) for studies describing an intervention designed to change health behaviour(s) among Pacific people. Titles and abstracts of 5699 papers were screened; 201 papers were then independently assessed. A review of full text was carried out by three of the authors resulting in 208 being included in the final review. Twenty-seven studies were included, published in six countries between 1996 and 2020. Results Important characteristics in the interventions included meaningful partnerships with Pacific communities using community-based participatory research and ensuring interventions were culturally anchored and centred on collectivism using family or social support. Most interventions used social cognitive theory, followed by popular behaviour change techniques instruction on how to perform a behaviour and social support (unspecified). Negotiating the spaces between Eurocentric behaviour change constructs and Pacific worldviews was simplified using Pacific facilitators and talanoa. This relational approach provided an essential link between academia and Pacific communities. Conclusions This systematic search and narrative synthesis provides new and important insights into potential elements and components when designing behaviour change interventions for Pacific people. The paucity of literature available outside of the United States highlights further research is required to reflect Pacific communities living in New Zealand, Australia, and the Pacific region. Future research needs to invest in building research capacity within Pacific communities, centering self-determining research agendas and findings to be led and owned by Pacific communities.